Protective effects of 18β-glycyrrhetinic acid on Pasteurella multocida–induced vascular inflammatory injury in mice - Lu, Qirong; Wang, Luyao; Jiang, Xueping; Han, Wantong; Guo, Pu; Liu, Yu; Fu, Shulin; Xiong, Jianglin; Wu, Zhongyuan; Qiu, Yinsheng (Frontiers in Veterinary Science, 2025)
Pasteurella multocida (Pm) is a widespread zoonotic pathogen with the ability to infect wild animals, livestock, and humans. Pm infection can cause haemorrhagic pneumonia, indicating that the pathogenesis involves serious vascular injury and inflammation. 18β-Glycyrrhetinic acid (GA) has cardiovascular protective and anti-inflammatory effects, but its effect on vascular injury caused by Pm infection is not clear. This study focused on the protective effects of GA on Pm-induced vascular inflammatory injury in mice. The results showed that GA intervention significantly improved the survival rate and the changes in haematological and biochemical parameters caused by Pm infection in mice. Haematoxylin and eosin staining revealed that GA delayed the progression of vascular injury, including abnormalities in elastic fibres, local rupture of the vascular intima, and inflammatory cell infiltration in response to Pm infection. The immunohistochemical results showed that after the GA intervention, the vascular inflammatory response in Pm-infected mice was alleviated. These protective effects may be related to the reduced expression of poly (ADP-ribose) polymerase-1, high mobility group box 1, interleukin-1β, and interleukin-18 in vascular tissue by GA. These findings suggest that GA inhibits the activation of inflammation to protect vascular injury in vivo. Hence, GA exhibits therapeutic potential in the treatment of vascular injury.